The Frontal Sinus and Frontal Recess: Anatomical, Radiological and Surgical Concepts - Dassi,Camila S. (2020)
Abstract Introduction The frontal sinus (FS) is the most complex of the paranasal sinuses due to its location, anatomical variations and multiple clinical presentations. The surgical management of the FS and of the frontal recess (FR) is technically challenging, and a complete understanding of its anatomy, radiology, main diseases and surgical techniques is crucial to achieve therapeutic success. Objectives To review the FS and FR anatomy, radiology, and surgical techniques. Data Synthesis The FS features a variety of anatomical, volumetric and dimensional characteristics. From the endoscopic point of view, the FR is the point of greatest narrowing and, to have access to this region, one must know the anatomical limits and the ethmoid cells that are located around the FR and very often block the sinus drainage. Benign diseases such as chronic rhinosinusitis (CRS), mucocele and osteomas are the main pathologies found in the FS; however, there is a wide variety of malignant tumors that can also affect this region and represent a major technical challenge to the surgeon. With the advances in the endoscopic technique, the vast majority of diseases that affect the FS can be treated according to Wolfgang Draf, who systemized the approaches into four types (I, IIa, IIb, III). Conclusion Both benign and malignant diseases that affect the FS and FR can be successfully managed if one has a thorough understanding of the FS and FR anatomy, an individualized approach of the best surgical technique in each case, and the appropriate tools to operate in this region.